Pirqei deRabbi Eliezer : structure, coherence, intertextuality - Keim, Katharina E., 1986- (Ancient Judaism and Early Christianity, 2017)
In Pirqei deRabbi Eliezer: Structure, Coherence, Intertextuality Katharina E. Keim offers a description of the literary character of Pirqei deRabbi Eliezer , an enigmatic work of the late-eighth-to-early-ninth centuries CE. Katharina E. Keim explores the work's distinctive literary features through an analysis of its structure and coherence. These literary features, when taken together with the work's intertextual relationships with antecedent and contemporaneous Christian and Jewish (rabbinic and non-rabbinic) texts, reveal Pirqei deRabbi Eliezer to be an innovative work, and throw light on a new turn in Jewish literature following the rise of Islam.